Application of computer simulation in mapping the drug delivery process in a network of pharmacies in the Minas Gerais triangle - de Araújo, Fernando; Pereira Oliveira, Fernanda; Arantes, Hialisson (Brazilian Journal of Production Engineering, 2020)
The present work aims to present a detailed research of the logistical processes of medication delivery mapped since the client's order in the order center until the release for delivery in the place informed by the client. The mapping was done so that the analysis is associated with a discrete modeling and simulation system correlated with each other, which can validate the hypotheses generated by the daily database of service times, thus generating more value in the relationship chain between the customer and the company. Anylogic tool version 8.3.2 was used, multi-method simulation software based on discrete events, agents and dynamical systems. Finally, as a result, processes were improved using the necessary tools in a pharmacy network at the delivery center, reducing delivery time and re-deliveries due to some divergence of information.
Keywords: Logistics; Anylogic; Modeling; Process Mapping; Discrete system simulation; Drugstore